Atrioventricular Conduction Disorders as a Complication of Inferior ST-Elevation Myocardial Infarction in Patients with COVID-19 Infection - Yaser Alahmad; Hassan Al-Tamimi; Fadi Khazaal; Mawahib Elhassan; Abdulrahman Arabi; Jassim Al Suwaidi; Awad AlQahtani; Nidal Asaad (Case Reports in Cardiology)
This case series demonstrates how COVID-19 infection might affect the heart in the context of acute myocardial infarction. Atrioventricular (AV) block might appear as one of the significant cardiac complications of acute MI in patients who tested COVID-19 PCR positive regardless of the presence of CVOID-19 infection symptoms. In our series, conduction disorders as a complication of acute inferior STEMI are more common in patients who tested positive for the COVID-19 infection. 11 patients out of 18 inferior STEMI patients who have tested positive for the COVID-19 infection have atrioventricular block disorders.